Tics in the Small Intestine: An Unusual Case of Jejunal Diverticulitis - William Dungan; John Romano; Puja Elias (Annals of Internal Medicine: Clinical Cases)
Small bowel (SB) diverticulosis is rare and usually has an asymptomatic presentation. Diverticular microperforations provoke inflammation and diverticulitis. Given the disease rarity, no current treatment guidelines exist. Little is known regarding malignancy-associated SB diverticulitis and screening with endoscopic procedures, capsule endoscopy, or radiographic imaging may be difficult or inadequate. In this case, we report on a 64-year-old woman who presented with abdominal pain secondary to jejunal diverticulitis, received antibiotics with radiographic disease resolution, and will undergo malignancy screening with balloon enteroscopy.